2021
DOI: 10.3389/fcell.2021.678127
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Orchestration of Anti-tumor Immune Responses: A Matter of Cell Localization and Communication

Abstract: The immune system plays a crucial role in cancer development either by fostering tumor growth or destroying tumor cells, which has open new avenues for cancer immunotherapy. It was only over the last decade that the role of B cells in controlling anti-tumor immune responses in the tumor milieu has begun to be appreciated. B and plasma cells can exert anti-tumor effects through antibody-dependent cell cytotoxicity (ADCC) and activation of the complement cascade, even though their effector functions extend beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 203 publications
1
71
0
Order By: Relevance
“…TRAF1 belongs to the Tumor necrosis factor receptor (TNFR)-associated factors (TRAF) protein family, which plays important roles in the immune system as key intracellular signaling molecules in TNFR, Toll-like receptor (TLR), cytokine and antigen receptor signaling pathways ( 19 ). TRAF1 expression in T and B lymphocytes can be induced by different stimuli that activate the transcription factor NF-κB ( 49 – 51 ), and may act as both positive and negative regulator of immune signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TRAF1 belongs to the Tumor necrosis factor receptor (TNFR)-associated factors (TRAF) protein family, which plays important roles in the immune system as key intracellular signaling molecules in TNFR, Toll-like receptor (TLR), cytokine and antigen receptor signaling pathways ( 19 ). TRAF1 expression in T and B lymphocytes can be induced by different stimuli that activate the transcription factor NF-κB ( 49 – 51 ), and may act as both positive and negative regulator of immune signaling.…”
Section: Discussionmentioning
confidence: 99%
“…the progressive loss of effector function due to chronic low-affinity antigen stimulation, is essential in maintaining immune homeostasis by regulating the duration and the magnitude of T cell responses, through a reduced proliferation, impaired effector functions, and elevated and sustained expression of multiple inhibitory receptors, known as immune checkpoint proteins (41). It is becoming progressively clear that the range of checkpoint inhibitors extends well beyond the few targets of current immunotherapy (41), and that functional exhaustion is not an exclusive matter of T lymphocytes, but heavily involves other immune cell populations (12,(42)(43)(44), that take part in mounting an effective immune response (19,45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between SLRs and immunotherapy outcomes in lung cancer seems not clear. On the other hand, although total TLS and germinal center-positive (GC+) TLS subset scores were demonstrated to predict survival in resected NSCLC patients ( 29 ), most studies suggested that only TLSs with GC were functional, and B cells in immature TLSs could adopt a regulatory phenotype and inhibit immune reactions ( 30 ). Moreover, we noted the predominant inhibitory Treg cells in post treatment tumor and PD-L1 expression in the lymph node for their crucial roles in immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in some cases, notably for HCC and GC, viral infections were associated with high levels of regulatory T cells ( Table 1 ). Notwithstanding, some cancers associated with viruses, such as HPV-associated HNSCC, have increased lymphoid aggregates composed of B and T cells known as tertiary lymphoid structures ( 127 , 129 ), which may serve as niches for antigen presentation in the TME and are associated with improved prognosis and response to ICB in multiple cancers ( 145 ).…”
Section: Exogenous Viruses As Triggers Of Anti-tumor Immune Responsesmentioning
confidence: 99%